Reconfigurable Intelligent Surfaces-Assisted Enhanced Spatial Modulation for Future Wireless Networks - Shaimaa Hussein Yasin; Osama A. Omer; Ahmed Mohammed Nor; Octavian Fratu; Simona Halunga; Ahmed S. Mubarak (IEEE Access, 2023)
Recently, reconfigurable intelligent surfaces (RISs) have been exhibited as a promising candidate for sixth generation (6G) wireless networks. Moreover, the concept of index modulation (IM) and its variants as spatial modulation (SM), has been adapted as another solution to improve the spectral efficiency (SE) and the energy efficiency (EE) for these wireless systems. Leveraging the inherent advantages of both SM and RIS, this paper proposes a dual hup RIS-based SM (DH RIS-SM) scheme. In addition, a novel RIS-based enhanced spatial modulation (RIS-ESM) scheme is proposed for further performance enhancement. In the proposed RIS-ESM scheme, information bits are conveyed by the indexes of the active antennas in addition to the constellations transmitted from each one of them with primary and secondary modulations, which in turns leads to significant improvements in both the SE and the EE. Moreover, for further EE enhancement, this paper proposes RIS-ESM- $P_{8}$ , as a variant of the proposed ESM scheme, in which the primary modulation is subdivided into two subgroups and the lower-energy subgroup is used in a larger number of combinations. A mathematical framework is presented by using a greedy detector for the calculation of the bit error probability (BEP) for the DH RIS-SM scheme. Also, the simulation results show that the proposed RIS-ESM schemes outperforms the conventional RIS-SM schemes in terms of the SE and the EE.